2016
DOI: 10.1007/s11069-016-2430-x
|View full text |Cite
|
Sign up to set email alerts
|

Rogue events in spatiotemporal numerical simulations of unidirectional waves in basins of different depth

Abstract: The evolution of unidirectional nonlinear sea surface waves is calculated numerically by means of solutions of the Euler equations. The wave dynamics corresponds to quasiequilibrium states characterized by JONSWAP spectra. The spatio-temporal data are collected and processed providing information about the wave height probability and typical appearance of abnormally high waves (rogue waves). The waves are considered at different water depths ranging from deep to relatively shallow cases (k p h > 0.8, where k p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…For rogue waves of moderate relative wave heights and wave steepness, numerical studies indicate no fundamental differences between rogue wave frequencies when upcrossing or downcrossing approaches were taken (e.g., Sergeeva and Slunyaev, 2013). However, for extreme rogue waves whose heights exceed 8σ in very steep wave conditions, numerical simulations suggested differences in frequencies when upcrossing or downcrossing definitions were used (Slunyaev et al, 2016). For in situ measurements, de Pinho et al (2004) reported increased rogue wave frequencies when zero upcrossing approaches were taken.…”
Section: Discussionmentioning
confidence: 99%
“…For rogue waves of moderate relative wave heights and wave steepness, numerical studies indicate no fundamental differences between rogue wave frequencies when upcrossing or downcrossing approaches were taken (e.g., Sergeeva and Slunyaev, 2013). However, for extreme rogue waves whose heights exceed 8σ in very steep wave conditions, numerical simulations suggested differences in frequencies when upcrossing or downcrossing definitions were used (Slunyaev et al, 2016). For in situ measurements, de Pinho et al (2004) reported increased rogue wave frequencies when zero upcrossing approaches were taken.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental condition the set of 2D rogue events could be collected if one follows the evolution of sea waves along a straight line (for example, having an array of wave gauges along the direction of wave propagation). The 2D rogue events were previously analyzed in the strongly nonlinear simulations of strictly collinear waves reported in [Sergeeva & Slunyaev, 2013;Slunyaev et al, 2016;Slunyaev & Kokorina, 2017]. The data from those simulations are used in the present work (see series A0 and E0 in Table 1; they are studied in Sec.…”
Section: Description Of the Approachmentioning
confidence: 99%
“…In this section we analyze the dataset of simulations of irregular strictly planar waves accumulated in our previous works [Sergeeva & Slunyaev, 2013;Slunyaev et al, 2016;Slunyaev & Kokorina, 2017], see series A0 and E0 in Table 1. In this case the procedure of selection of the rogue events is equivalent to collecting 2D rogue wave events as described above.…”
Section: Rogue Wave Lifetimes In the Simulations Of Unidirectional Wavesmentioning
confidence: 99%
“…The asymmetry between the troughs from the rear and front sides of rogue waves is the particular object of the present study. In our previous simulations of unidirectional waves the typical picture of a rogue waves possesses the trend that most of the rogue waves where characterized by deeper rear troughs (Sergeeva & Slunyaev, 2013;Slunyaev et al, 2016). In the present work we broaden the discussion of the rogue wave frontto-crest asymmetry to the directional case (Slunyaev & Kokorina, 2020).…”
mentioning
confidence: 78%